Induced seismicity or political ploy?: Using a novel mix of methods to identify multiple publics and track responses over time to shale gas policy change. (November 2021) - Devine-Wright, P.; Ryder, S.; Dickie, J.; Evensen, D.; Varley, A.; Whitmarsh, L.; Bartie, P.
Highlights: Public responses to policy change involve awareness, interpretations and opinions. High public awareness and support exists towards the 2019 shale gas moratorium. Sceptical interpretations arose from the timing, source and extent of policy change. Social media analysis enables insight into public responses over hours and days. Mixed methods enables insights into diverse publics and drivers of ideology, scale and demographics. Abstract: To date, little research has investigated how public perceptions of policies to ban or restrict fossil-fuel extraction change over time; yet this topic is of crucial importance as countries worldwide seek to transition towards 'net zero' economies. This study addresses this gap by focusing on public responses to the 2019 moratorium on shale gas extraction in England, using an analytical framework comprising awareness, interpretations and opinions, and a mixed-method approach combining national survey, social media and local case interviews. Findings show high levels of awareness and support for the moratorium, yet differences between coalitions of interest based on ideology, scale and demographics. Social media analyses reveal a peak in public response across several days during a general election campaign in which different parties took divergent positions on shale gas. Public support for the moratorium – and induced seismicity as the primary reason for its introduction - was evidenced by the national survey, yet coincided with scepticism about its timing, extent and motivation, as indicated by social media activity and local case interviews. For some publics, the moratorium was a ploy to ensure electoral support, embedded in public distrust. This study indicates the merits of a mixed-method approach to understand the psychological and institutional context of public responses to policy change as it unfolds over time, and discusses the longer term implications of politicised attitudes for energy transitions.